2017
DOI: 10.1007/s13197-017-2555-2
|View full text |Cite
|
Sign up to set email alerts
|

Study on E. coli and Salmonella biofilms from fresh fruits and vegetables

Abstract: Foodborne outbreaks associated with fresh fruits and vegetables are on the rise worldwide. Biofilm formation is one of the important traits of pathogens making them strongly attached to substrates as well as express virulence phenotypes. Present study investigates the biofilm forming ability of E. coli and Salmonella sp. isolated from fresh fruits and vegetables. A total of 53 strains, including 35 E. coli and 18 Salmonella sp. isolated from different fruit and vegetable samples were taken into account for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…While 2 (8.7%) E. coli isolates were recognized as saw morphotypes and did not produce biofilm. The current results were in accordance to previous authors that described the correlation between a phenotypic appearance on congo red agar and biofilm formation (Bokranz et al, 2005;Milanov, Prunic, Velhner, Todorovic et al, 2015;Amrutha et al,2017). Bokranz et al (2005) demonstrated that E. coli strains expressing rdar morphotype showed a higher capacity to form biofilms than saw strains.…”
Section: Quantitative Biofilmsupporting
confidence: 93%
“…While 2 (8.7%) E. coli isolates were recognized as saw morphotypes and did not produce biofilm. The current results were in accordance to previous authors that described the correlation between a phenotypic appearance on congo red agar and biofilm formation (Bokranz et al, 2005;Milanov, Prunic, Velhner, Todorovic et al, 2015;Amrutha et al,2017). Bokranz et al (2005) demonstrated that E. coli strains expressing rdar morphotype showed a higher capacity to form biofilms than saw strains.…”
Section: Quantitative Biofilmsupporting
confidence: 93%
“…isolated from humans, animals, or food [5,33]. Amrutha et al [36] reported that 50% of Salmonella spp. isolated from different fruits and vegetables were strong biofilm producers/ while the rest were found to be moderate or weak biofilm producers.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation starts with the microbial adhesion to the plant, being accessible for the bacteria that have flagella, allowing chemotaxis and swimming motility for colonization through surface adhesion ( McLandsborough et al, 2006 ). Researchers have demonstrated that Bacillus, Salmonella, Listeria, Staphylococcus, and Escherichia presented in FV are capable of biofilm formation, which is crucial for the virulence of the pathogenic strains ( Amrutha et al, 2017 ). Recently, Sun, Ye, et al (2021) demonstrated that E. coli O157:H7 formed a denser biofilm on cucumber tissues, especially in the vascular tissues.…”
Section: Microbial Contaminationmentioning
confidence: 99%